1997
DOI: 10.2307/1592462
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Production of Ascites in Broiler Chickens Using Infectious Bronchitis Virus and Escherichia coli

Abstract: Common commercial strain male broilers were intratracheally inoculated with 0.3 ml of fluid containing 10(3.7) embryo infective doses of infectious bronchitis virus (IBV) at 14 days of age and 7.5 x 10(6) colony-forming units of Escherichia coli at 18 days of age. Ascites was detected in 15 out of 100 infected birds, which was significantly higher than in a control group of 100 mock-infected birds (P < 0.01). Some parabronchi were blocked by copious exudate containing heterophils and fibrin in the infected bir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 21 publications
0
9
0
1
Order By: Relevance
“…Ascites outbreaks have been attributed in several reports to poor air quality (e.g., dusty conditions), poor ventilation (e.g., elevated ammonia, carbon monoxide, or carbon dioxide levels), and respiratory damage or airway obstruction due to pathogens or pulmonary inflammation (Wideman, 1984(Wideman, , 1988Julian and Goryo, 1990;Shlosberg et al, 1992Shlosberg et al, , 1996aBottje and Wideman, 1995;Tottori et al, 1997;Wideman et al, 1997;Bottje et al, 1998). Exposure to bacterial lipopolysaccharide (LPS, endotoxin) has been used to experimentally simulate the responses of broiler lungs to inflammatory responses.…”
Section: Mediators Of Pulmonary Vasoconstrictionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ascites outbreaks have been attributed in several reports to poor air quality (e.g., dusty conditions), poor ventilation (e.g., elevated ammonia, carbon monoxide, or carbon dioxide levels), and respiratory damage or airway obstruction due to pathogens or pulmonary inflammation (Wideman, 1984(Wideman, , 1988Julian and Goryo, 1990;Shlosberg et al, 1992Shlosberg et al, , 1996aBottje and Wideman, 1995;Tottori et al, 1997;Wideman et al, 1997;Bottje et al, 1998). Exposure to bacterial lipopolysaccharide (LPS, endotoxin) has been used to experimentally simulate the responses of broiler lungs to inflammatory responses.…”
Section: Mediators Of Pulmonary Vasoconstrictionmentioning
confidence: 99%
“…The respiratory tract is constantly challenged with aerosolized bacteria (e.g., poultry house "dust") or bacteria translocated into the blood from the gastrointestinal tract or integument. Administering LPS intravenously or via an inhaled aerosol triggers pulmonary hypertension attributable to vasoconstriction (Wideman et al, , 2009Chapman et al, 2005Chapman et al, , 2008Lorenzoni and Wideman, 2008b), and respiratory exposure to E. coli amplifies the incidence of PAH (Tottori et al, 1997;Yamaguchi et al, 2000). The pulmonary hypertension elicited by LPS in mammals has been associated with the release or synthesis of several vasoconstrictors, including ET-1, platelet activating factor, TxA 2 , and 5-HT .…”
Section: Mediators Of Pulmonary Vasoconstrictionmentioning
confidence: 99%
“…Respiratory disease could cause hypoxic hypoxaemia and induce polycythaemia (Tottori et al, 1997). Fibrosis following lung damage from infection and inhaled or ingested toxins can reduce capillary size, restricting blood flow and causing PH (Julian, 1993;Witschi, 1996).…”
Section: The Lungs and Air Sacs As Physiological Triggers Of The Asmentioning
confidence: 99%
“…The heritability of RV:TV is approximately half that of the clinical condition of ascites (Lubritz et al, 1995). It has been demonstrated that elevated RV:TV ratios can be induced by the experimental intratracheal inoculation of infectious bronchitis virus or Escherichia coli (Tottori et al, 1997). These agents could not be recovered from the birds by the time the clinical signs of ascites developed.…”
Section: The Role Of Infectious Agentsmentioning
confidence: 99%